Ideologi Pendidikan Pondok Pesantren Al-Islam Tenggulun Solokuro Lamongan - Taufik Nugroho (Universitas Cokroaminoto Yogyakarta, 2019)
This research is motivated by the fact that there are some pesantren alumni and their caregivers involved in acts of radicalism. Based on the facts above, the researcher is interested in conducting research on the ideological aspects. Many people believe that a person's actions are guided and validated by the ideology he believes in. For this reason the question arises, ‘what is the ideology of education in the pesantren al-Islam, Tenggulun, Solokuro?